Le patrimoine sans le tourisme ? Les roches gravées de Guadeloupe (Antilles) - Mélanie Duval; Christophe Gauchon; Julien Monney (Études Caribéennes)
The Guadeloupean archipelago hosts the most significant collection of pre-Columbian rock art in the Lesser Antilles. Despite its recognized heritage status, through protection as French Historic Monuments, this rock art has seen limited activation as a touristic resource. This study aims to understand this gap by analyzing the role occupied by the rock art in Guadeloupe’s current and past tourist landscape. Implementing a systemic approach that integrates qualitative and quantitative data, we reveal the multifactorial nature of the current situation: spatial disjunction between rock art sites and major tourist infrastructures, competition with other cultural themes such as the history of slavery, and differing perceptions among heritage stakeholders regarding the place of pre-Columbian rock art in tourist development. The results also indicate that tourist and heritage development strategies around Guadeloupe’s rock art are not solely driven by mediation efforts aimed at external tourists. They are also shaped by internal needs for valorization, giving rise to distinct forms of mediation linked to specific heritage relationships, and identity and educational issues akin to those prevalent in contemporary Caribbean societies.